2019
DOI: 10.3390/microorganisms8010062
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptive Morphology of Bacillus subtilis Biofilms: A Defense Mechanism against Bacterial Starvation

Abstract: Biofilms are commonly defined as accumulations of microbes, embedded in a self-secreted, polysaccharide-rich extra-cellular matrix. This study aimed to characterize specific morphological changes that occur in Bacillus subtilis biofilms under nutrient-limiting growth conditions. Under varying levels of nutrient depletion, colony-type biofilms were found to exhibit different rates of spatial expansion and green fluorescent protein production. Specifically, colony-type biofilms grown on media with decreased lyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…For example, Wilking et al [ 29 ] suggested that the abovementioned network of channels facilitates liquid transport throughout the macrocolonies with evaporative flux acting as the driving force. A complementary force that allows the macrocolonies to uptake nutrients from the growth substrate was also suggested by Gingichashvili et al [ 12 ], while a similar channel-driven nutrient uptake and distribution effect was previously reported in E. coli biofilms [ 30 ]. Analysis of macrocolonies that were co-cultured and grown in a mixture with fluorescent microspheres reveals two additional forces present in B. subtilis macrocolonies.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…For example, Wilking et al [ 29 ] suggested that the abovementioned network of channels facilitates liquid transport throughout the macrocolonies with evaporative flux acting as the driving force. A complementary force that allows the macrocolonies to uptake nutrients from the growth substrate was also suggested by Gingichashvili et al [ 12 ], while a similar channel-driven nutrient uptake and distribution effect was previously reported in E. coli biofilms [ 30 ]. Analysis of macrocolonies that were co-cultured and grown in a mixture with fluorescent microspheres reveals two additional forces present in B. subtilis macrocolonies.…”
Section: Discussionsupporting
confidence: 63%
“…At the same time, the intermediate region where filaments are tightly packed provides the strongest attachment while the leading zone is again more loosely attached at the leading edge of the biofilm. Under limited nutrient supply, the topographical changes that occur at the contact surface may drive the accelerated expansion of the macrocolonies—their wider and less tightly packed filaments might help explain the enhanced spreading ability of such colony type biofilms [ 12 ] as they are likely to result in looser adhesion at the contact surface, which is further supported by profilometry data results.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Our findings suggest that evolution may select for the optimal colony morphology, which is a macroscopic, population-level property resulting from cellular-level interactions. The formation of multicellular and macroscopic structures by microbial communities that benefit the population as a whole is widely observed; other examples include the formation of patches (Ratzke & Gore, 2016), filaments (Pfeffer et al, 2012), spore-filled fruiting bodies (Munoz-Dorado et al, 2016), and biofilms with intricate structures (Epstein et al, 2011;Wilking et al, 2013;Kempes et al, 2014;Gingichashvili et al, 2019). These social traits of microbes reflect intercellular cooperation and coordination, which are the hallmarks of multicellularity (Shapiro, 1988;Lyons & Kolter, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, adhesion of particles to each other or to a target site is a central aim in different applications. ii. Protection from environment: Biofilms help microorganisms to protect themselves in extreme environments (Yin et al ., 2019), against ultraviolet radiation (UV) (de Carvalho, 2017), extreme temperatures (Smith et al ., 2016; Kent et al ., 2018), pH variations (Narayanan et al ., 2016), salinity or drought stress (Alaa, 2018; Wang et al ., 2019) and limitation of nutrients (Gingichashvili et al ., 2020). In general, a biofilm can be described as a protective matrix in which both the polysaccharide‐producing microorganisms and co‐living cells are encapsulated.…”
Section: Microbial Polysaccharides: Functionalities and Their Applicability In Industrymentioning
confidence: 99%